WIND ENERGY FOR VILLAGERS TO REDUCE POLLUTION AND THE USE OF FOSSIL FUEL - nashar, muhamad (Agency for the Assessment and Application of Technology)
Wind energy potential in Indonesia is about 450.000 MW. The Heritage Bogor Foundation (HBF) is trying to contribute the use of renewable energy by introducing wind energy technology. The project has been starting since 2003, to conduct a research and development of wind energy technology for water pumping/ irigation and village electricity. The designed windmill was made as simple as possible and used local materials to make it affordable. This paper described wind data collection in the targeted area, the development stages and the benefit analysis for villagers.